(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The purpose of this study is to analyse pragmatics of the epistolary technique, or the use of letters in biographical works. Moreover, It investigates pragmatic considerations for using this technique in biographical writing. Incorporating these pragmatic considerations can help ensure that the epistolary technique enhances the biographical work.